Activity-Dependent Plasticity of Spinal Circuits in the Developing and Mature Spinal Cord - Behdad Tahayori; David M. Koceja (Neural Plasticity)
Part of the development and maturation of the central nervous system (CNS) occurs through interactions with the environment. Through physical activities and interactions with the world, an animal receives considerable sensory information from various sources. These sources can be internally (proprioceptive) or externally (such as touch and pressure) generated senses. Ample evidence exists to demonstrate that the sensory information originating from large diameter afferents (Ia fibers) have an important role in inducing essential functional and morphological changes for the maturation of both the brain and the spinal cord. The Ia fibers transmit sensory information generated by muscle activity and movement. Such use or activity-dependent plastic changes occur throughout life and are one reason for the ability to acquire new skills and learn new movements. However, the extent and particularly the mechanisms of activity-dependent changes are markedly different between a developing nervous system and a mature nervous system. Understanding these mechanisms is an important step to develop strategies for regaining motor function after different injuries to the CNS. Plastic changes induced by activity occur both in the brain and spinal cord. This paper reviews the activity-dependent changes in the spinal cord neural circuits during both the developmental stages of the CNS and in adulthood.